1998
DOI: 10.1073/pnas.95.17.10240
|View full text |Cite
|
Sign up to set email alerts
|

A sensory neuron-specific, proton-gated ion channel

Abstract: Proton-gated channels expressed by sensory neurons are of particular interest because low pH causes pain. Two proton-gated channels, acid-sensing ionic channel (ASIC) and dorsal root ASIC (DRASIC), that are members of the amiloride-sensitive ENaC͞Degenerin family are known to be expressed by sensory neurons. Here, we describe the cloning and characterization of an ASIC splice variant, ASIC-␤, which contains a unique N-terminal 172 aa, as well as unique 5 and 3 untranslated sequences. ASIC-␤, unlike ASIC and DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
333
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(349 citation statements)
references
References 31 publications
(48 reference statements)
11
333
1
4
Order By: Relevance
“…For the nervous systems, differences in the localization of ASIC subtypes have been reported: all ASIC subtypes were observed in the peripheral nervous system (PNS) while ASIC1a, 2a and 2b were found in the spinal cord and ASIC1a, 2a and 4 in the brain (Price et al, 1996;Chen et al, 1998;Babinski et al, 2000;Peng et al, 2004;Lingueglia, 2007). We also reported that ASIC2 expression was detected in the ciliated cells of the rat trachea although the subtypes were not clarified in our previous study (Kikuchi et al, 2008).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For the nervous systems, differences in the localization of ASIC subtypes have been reported: all ASIC subtypes were observed in the peripheral nervous system (PNS) while ASIC1a, 2a and 2b were found in the spinal cord and ASIC1a, 2a and 4 in the brain (Price et al, 1996;Chen et al, 1998;Babinski et al, 2000;Peng et al, 2004;Lingueglia, 2007). We also reported that ASIC2 expression was detected in the ciliated cells of the rat trachea although the subtypes were not clarified in our previous study (Kikuchi et al, 2008).…”
Section: Discussionmentioning
confidence: 66%
“…Among them, ASIC1 and ASIC2 have spliced variants. The ASIC1 gene spliced variants are ASIC1a and ASIC1b, and ASIC2 spliced variants are ASIC2a and ASIC2b (Lingueglia et al, 1997;Waldmann et al, 1997;Chen et al, 1998;Bassler et al, 2001). No spliced variants of ASIC3 or ASIC4 have been detected.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conducting Na + ions, homomeric ASIC1a channels are permeable to Ca 2+ ions [10,12,13]. ASIC1b (ASIC1β) is a splice variant of ASIC1a with restricted expression in sensory neurons [24]. Homomeric ASIC1b channels respond to pH o drop with a similar transient current and a pH 0.5 of ∼5.9 [24,25].…”
Section: Tissue Distribution and Electrophysiological Properties Of Amentioning
confidence: 99%
“…ASIC1b (ASIC1β) is a splice variant of ASIC1a with restricted expression in sensory neurons [24]. Homomeric ASIC1b channels respond to pH o drop with a similar transient current and a pH 0.5 of ∼5.9 [24,25]. Unlike ASIC1a, homomeric ASIC1b channels do not show Ca 2+ permeability.…”
Section: Tissue Distribution and Electrophysiological Properties Of Amentioning
confidence: 99%
See 1 more Smart Citation